Treatise on geomorphology - Shroder, John F., 1939- (Academic Press, 2013)
Provides context for ongoing research, includes discussion of research strategies, equipment, and field methods, laboratory experiments, and numerical simulations to reflect multiple approaches to understanding Earth's surfaces. Summaries include outstanding research questions highlighting future challenges and suggest productive new avenues for research.